EVALUASI TINGKAT KEPATUHAN IMPORTIR ATAS MEKANISME SELF ASSESSMENT BARANG KIRIMAN HASIL TRANSAKSI PERDAGANGAN DENGAN NILAI PABEAN SAMPAI DENGAN FOB USD 1.500 - Disa Agnesia Utari L. Tobing; Siti Nuryanah (Politeknik Negeri Ambon, 2026)
Introduction: The Indonesian government has enacted new regulations for goods shipped from trade transactions, including Self Assessment, through the Minister of Finance Regulation Number 96 of 2023. This policy has led to manipulation through undervaluation, prompting the government to impose fines for tax evasion. Methods: This study aims to evaluate the extent of importer compliance with the Self Assessment mechanism for goods shipped, using a Fishbone Diagram. This research is a qualitative study employing descriptive analysis and triangulation. Results: Data obtained from interviews with sources from the Directorate General of Customs and Excise and from analysis of imported goods shipment data indicate that importers have complied with existing regulations, but several improvements are needed, such as an application that provides the status of the goods shipment completion process and the socialisation of customs obligation calculations. Keywords: Compliance, Courier Service, Customs, Import, Tax